Transform the expression:
"P \\to ((P \\to Q) \\land \\lnot(\\lnot Q \\lor \\lnot P))"
Expressing the conditional using logical-or and using De Morgan's law:
"P \\to ((\\lnot P \\lor Q) \\land Q \\land P)"
Using the absorbtion law:
"P \\to (Q \\land P)"
Expressing the conditional using the logical or:
"\\lnot P \\lor (Q \\land P)"
Using the distibutive law:
"(\\lnot P \\lor Q) \\land (\\lnot P \\lor P)"
"(\\lnot P \\lor Q) \\land T"
"\\lnot P \\lor Q"
Make a truth table:
"P \\ \\ \\ \\ Q \\ \\ \\ \\ \\ \\lnot P \\lor Q"
"F \\ \\ \\ \\ F \\ \\ \\ \\ \\ T"
"F \\ \\ \\ \\ T \\ \\ \\ \\ \\ T"
"T \\ \\ \\ \\ F \\ \\ \\ \\ \\ F"
"T \\ \\ \\ \\ T \\ \\ \\ \\ \\ T"
For the rows that have the expression true do the following to obtain the PDNF:
For each row right down all the variables in the expression, if the variable has False value in this row, negate it. Make a conjunction of these terms.
Each such conjuction unite in the complete expression using a disjunction.
For the required expression there are 3 such conjunctions:
"(P\u2227Q)"
"(\u00acP\u2227Q)"
"(\u00acP\u2227\u00acQ)"
Therefore, the PDNF is:
"(P\u2227Q)\u2228(\u00acP\u2227Q)\u2228(\u00acP\u2227\u00acQ)"
Answer: "(P\u2227Q)\u2228(\u00acP\u2227Q)\u2228(\u00acP\u2227\u00acQ)"
Comments
Leave a comment